1986
DOI: 10.1159/000262269
|View full text |Cite
|
Sign up to set email alerts
|

In utero Bladder Diversion – Problems with Patient Selection

Abstract: Based upon the concept that an obstruction-maldevelopment sequence is reversible after diversion, it has been suggested that the fetus with a bladder outlet obstruction is a potential candidate for in utero intervention. We report an infant who had both renal and pulmonary dysplasia at birth despite a technically successful diversion at 22 weeks’ gestation. The poor outcome suggests that the organ damage either occurs so early that it precludes corrective surgery, or that the maldevelopment is not the result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Not all investigators have found that the current selection criteria for intrauterine vesi coamniotic shunting assures proper case se lection [12][13][14], These reports have indicated that despite evidence of good renal function, and a functioning vesicoamniotic shunt, in fants were still being born with renal dyspla sia. and some died as a result of this severe sequela.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all investigators have found that the current selection criteria for intrauterine vesi coamniotic shunting assures proper case se lection [12][13][14], These reports have indicated that despite evidence of good renal function, and a functioning vesicoamniotic shunt, in fants were still being born with renal dyspla sia. and some died as a result of this severe sequela.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have questioned whether these selection criteria are always reflective of the true renal function, and thus whether renal dysplasia is present or absent [12][13][14]. Vesicoamniotic shunting has an associated procedure-related death rate of 8% [15].…”
Section: Introductionmentioning
confidence: 99%